Новый вид цестод — Diphyllobothrium macroovatum sp. n. (Cestoda, Diphyllobothriidae) — паразит серого кита - Юрахно, М.В. (Вестник зоологии, 1973)
The cestoda Diphyllobothrium macroovatum Sp. n. from the intestine of Eschrichtius gibbosus E r x 1 e ben inhabiting the Bering sea is described. New species differ from all other species of the genus Diphyllobothrium Co b b o 1 d, 1858 by rather greater dimensions of eggs (0.084-0.096X0.040-0.054 mm) and form of scolex. It has some af- finity with D. stemmacephalum (C o b b o I d, 1858), D. cordatum (L e u c k a r t, 1863) and D. polyrugosum Del a m u r e et A. S k r i a b i n, 1966. But however the new species differs from those above-mentioned in many anatomical and morphological characters in the host and (except for D. cordatum) by the other area of distribution.